One-Way Mirrors in Online Dating: A Randomized Field Experiment - Bapna, Ravi; Ramaprasad, Jui; Shmueli, Galit; Umyarov, Akhmed (Management Science, 2016)
The growing popularity of online dating websites is altering one of the most fundamental human activities: finding a date or a marriage partner. Online dating platforms offer new capabilities, such as extensive search, big data–based mate recommendations, and varying levels of anonymity, whose parallels do not exist in the physical world. Yet little is known about the causal effects of these new features. In this study we examine the impact of a particular anonymity feature, which is unique to online environments, on matching outcomes. This feature allows users to browse profiles of other users anonymously, by being able to check out a potential mate’s profile while not leaving any visible online record of the visit. Although this feature may decrease search costs and allow users to search without inhibition, it also eliminates “weak signals” of interest for their potential mates that may play an important role in establishing successful communication. We run a randomized field experiment on a major North American online dating website, where 50,000 of 100,000 randomly selected new users are gifted the ability to anonymously view profiles of other users. Compared with the control group, the users treated with anonymity become disinhibited, in that they view more profiles and are more likely to view same-sex and interracial mates. However, based on our analysis, we demonstrate causally that weak signaling is a key mechanism in achieving higher levels of matching outcomes. Anonymous users, who lose the ability to leave a weak signal, end up having fewer matches compared with their nonanonymous counterparts. This effect of anonymity is particularly strong for women, who tend not to make the first move and instead rely on the counterparty to initiate the communication. Further, the reduction in quantity of matches by anonymous users is not compensated by a corresponding increase in quality of matches. This paper was accepted by Lorin Hitt, information systems.